THE EFFECTIVENESS OF IMPLEMENTATION WARMER APPERCEPTION TO CONSTRUCT THE CONCEPTUAL UNDERSTANDING ON THE LEARNING MATERIAL OF VECTOR - Rohmah, Riska Nur; Utomo, Dwi Priyo; Zukhrufurrohmah, Zukhrufurrohmah (Study Program of Mathematics Education University of Muhammadiyah Malang, 2019)
One of the learning stages is apperception. Warmer apperception is an activity that conducted to make the students? knowledge to be stored in long-term memory. This research aimed at: 1) describing the learning implementation using Warmer apperception to construct a conceptual understanding in the vector material, 2) determining the effectiveness of the implementation of Warmer apperception to construct a conceptual understanding in the vector material. The effectiveness of learning using Warmer apperception could be seen from: 1) the observation of learning implementation using Warmer apperception that indicated a minimum of the sufficient category; 2) the students? response questionnaire indicated a minimum of positive response category; and 3) the test results of students? conceptual understanding indicated a minimum of quite a good category. The subjects of this research were the students of 10th grade of Mathematics and Natural Science (MIA) at Senior High School (SMA) of Muhammadiyah 3 Batu, in which it consisted of 21 students. Based on the research conducted, it was obtained that the observation results of learning implementation using Warmer apperception got a very good category, the questionnaire results obtained a positive response category, and the test results of students? conceptual understanding got a quite good category. Thus, the implementation of Warmer apperception to construct a conceptual understanding of the vector material is effective..